The Society of the Performance. The Masked Man - Nahapetyan, Ovsanna (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
Events in the modern world seem to have disrupted the objective sense of time. In our world of "fast times", such radical socio-cultural transformations are taking place, which not only devalue the role and importance of once-in-a-lifetime customs, traditions and moral norms, but also weaken and impoverish social integrity. Essentially, humanity is living in a world that is a peculiar mixture (symbiosis) of objective, subjective, virtual and illusory realities, and where the man of organized society is imperceptibly transformed into a man-decor of various social performances, who is obliged to fulfill the role assigned to him in each creation. wear a mask.Ontologically, it is perhaps difficult to separate a person from his mask, because it is formed along with the socialization of the human personality. Ultimately, an individual becomes a person when he adopts certain social roles and their corresponding social masks provided by the culture of organization of life in a given society. From this point of view, it can be said that the social role and the corresponding mask not only clearly outline the boundaries of the seeming, the formal and the real, which is a constant companion of human life, which is an important condition of self-perception, but also plays the role of bridging the inner world of a person with the outside world. As a result, as they say, any face becomes a freely chosen mask, and the mask becomes a public face.
Keywords: performance society; virtual reality; face; role; mask; social game; role behavior